Innovation and Productivity of Vietnamese Small and Medium Enterprises: Firm level panel data evidence - Pham Dinh Long; Ho Thi Mai Anh (International Journal of Economics and Financial Issues, 2017)
Innovation is considered as a driver of productivity at both country and firm level. However, the researches on the relationship between innovation and firm productivity in Vietnam are rare. Using Vietnam's SMEs survey in 2007 and 2009, this paper examines this relationship for the small and medium enterprises (SMEs). Cobb-Douglas production function and the fixed effect model are employed throughout the paper. We find that the presence of innovation has positive effects on firm productivity. In addition, this study also looks at the impact of firm size, firm location and manufacturing sector on the relationship between innovation and SMEs' productivity.